Corporate governance mechanisms and intellectual capital - Tejedo-Romero, Francisca; Filipe Ferraz Esteves Araujo, Joaquim; Emmendoerfer, Magnus Luiz (Review of Business Management, 2017)
Purpose – The purpose of this paper is to identify the corporate governance characteristics of Spanish companies included in the Ibex35 stock price index that influence the voluntary information disclosure policy regarding their Intellectual Capital. Design/methodology/approach – The methodology used was content analysis of 115 annual reports from 23 Ibex35 companies over five years; this allowed for the development of an index to quantify Intellectual Capital information. Findings – Based on Agency-Stakeholders Theory postulates, the main results reveal that companies that disclose most information about their Intellectual Capital are those in which managers have greater managerial ownership, fewer independent directors, separation of functions between the chairman and the chief executive, and larger Boards of Directors. Originality/value – With this study, we contribute to agency-stakeholder theory by analyzing a non-Anglo-Saxon market (characterized by strong executive power and low protection of minority shareholders and other stakeholders), stating that certain characteristics of Corporate Governance condition the disclosure of Intellectual Capital.